Right to have rights : citizenship, humanity and international law - Kesby, Alison (OUP OxfordGB, 2012)
Explores two overarching questions, i) how do different and competing conceptions of the right to have rights shed light on right-bearing in the contemporary context, and in particular on concepts and relationships central to the protection of human rights in public international law and ii) how is the right to have rights to be understood in the context of international law and, what is the significance of this concept for international legal thought and practice today?